Role of 18F-fluorodeoxyglucose positron emission tomography/computed tomography and magnetic resonance imaging in prediction of response to neoadjuvant chemotherapy in pediatric osteosarcoma - Younis, Jehan Ahmed; Al Antably, Ismael Mohammed; Zamzam, Manal; Salem, Hala Taha; Zaki, Eman Mohammed; Hassanian, Omneya Ahmed (World Journal of Nuclear Medicine, 2019)
The aim of our study was to evaluate the role of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) and magnetic resonance imaging (MRI) in prediction of response to neoadjuvant chemotherapy (NAC) in pediatric osteosarcoma (OS) patients compared to percentage of tumor necrosis after surgical excision of the tumor. Forty-six pediatric OS patients treated with neoadjuvant chemotherapy and surgery were underwent PET/CT and MRI before, after 3 cycles, and after the completion of neoadjuvant chemotherapy. Imaging parameters include maximum standardized uptake value (SUVmax1, 2, and 3), tumor liver ratio (TLR 1, 2, and 3), and MRI tumor volume (MRTV 1, 2, and 3) at initial assessment before starting NAC, after finishing three cycles and after finishing 6 cycles before tumor excision, respectively. Cutoff values of the PET/CT and MRI parameters were determined using receiver operating characteristic (ROC) curve analysis and percentage of tumor necrosis of postsurgical specimen. Fourteen patients were good responders (30.4%), with more than 90% tumor necrosis, while 31 patients were poor responders (67.4%). The results of one patient were missed. We noticed that higher sensitivity for detecting poor responders was detected by SUVmax3/1, TLR3/1, and MRTV2/1 ratio cutoff values, while higher specificity was detected by TRL2 and SUVmax3 cutoff values. ROC curve analysis of MRTV2/1 and MRTV3/1 ratio was fair in predicting poor responders. PET/CT parameters are capable of predicting histological response to NAC in OS patients with overall sensitivity and specificity higher than MRI parameters.
Keywords: 18F-fluorodeoxyglucose positron emission tomography/computed tomography; magnetic resonance imaging; neoadjuvant chemotherapy; osteosarcoma